Macgregor Brides - Roberts, Nora (New York, NY Silhouette Books, 1997)
The illustrious MacGregor clan's irresistible patriarch--and relentless matchmaker--is determined to have his three lovely granddaughters engaged by Christmas and has handpicked three unsuspecting gentlemen as their prospective mates.
"This edition published by arrangement with Harlequin Books S.A" - T.p. verso
79486
Keywords: Contemporary Romance; Love stories